Characterization of sediments in fish farming ponds in the Eastern Amazon, Brazil (Research, Society and Development, 2021)
The objective of the study was to characterize the pond sediment with fish and without fish from the estuarine lowland of the Eastern Amazon, Pará, Brazil, after liming and fertilizing. Tambaquis (Colossoma macropomum) were used, with an average total length of 3.19cm and an average total weight of 0.28g. The treatments were estuarine lowland ponds that received liming, fertilization and fish (T1); nurseries with liming and without fish (T2); and, nurseries without any preparation and with fish (T3). Liming for asepsis and pH correction was carried out with hydrated magnesium lime and PRNT 90% in the amount of 1000 kg ha-1. In addition, fertilization with organic manure (tanned manure from birds) in the amount of 1000 kg ha-1, after. The average pH was significantly higher in sediments (T1), followed by treatments T2 and T3, respectively. Exchangeable organic carbon, Mg+2 and Al+3 were higher (p